Screening of Antibiotic Producing Actinomycetes for Antibiosis from Soil of Siraha, Nepal - Sah, Shiv Nandan; Lekhak, Binod (Himalayan Journal of Science and Technology, 2017)
The increasing need of novel antibiotics has provided a pace for the search of antibiotics from actinomycetes. Primary and secondary screenings of antibiotic producing actinomycetes from the soil of Siraha (75-600 m) were performed. The minimum inhibitory concentration of the metabolites was determined against E. coli. Macroscopic, microscopic and biochemical characterization were performed for the identification of presumptive genera. Characterization of the antibacterial substances was done by TLC. Among 92 isolates, 22 showed antibacterial activity against at least 1 bacterium out of 6 test bacteria used. Microscopy and other characteristics studies revealed that 19 (86.36%) were Streptomyces spp.,1 (4.55%) was Thermomonospora spp., and 2 (9.09 %) were unidentified. Five potent isolates were selected for the secondary screening where 2 isolates inhibited Gram negative bacteria with an MIC value of 1.2 mg/mL for each isolate. TLC showed that both antibiotics produced only one spot suggesting the presence of one active compound other than vancomycin (standard). The active isolates from primary screening were heterogeneous in their overall macroscopic, biochemical, and physiological characteristics. The two potent isolates showing antibacterial activity were found to belong to different distinct taxonomic groups.